2018
DOI: 10.1111/jace.15348
|View full text |Cite
|
Sign up to set email alerts
|

Efficient red‐emitting phosphor of Eu3+‐activated (Na0.5Gd1.5)(TiSb)O7 derived via cation‐substitutions in Gd‐Pyrochlore

Abstract: Rare‐earth (RE) titanate pyrochlore with perovskite‐layered structure is a well‐known engineering material in applied in many field. In this work, a red‐emitting phosphor of Gd2−xNaxTi2−2xSb2xO7:Eu3+ (x = 0‐0.5) was developed via cation substitutions of (Sb5+→Ti4+) and (Na+→Gd3+) in Gd2Ti2O7. The motivation is based on the fact that the introduction of cation‐disorders has been regarded to be an effective approach for improving the luminescent efficiency and thermal stability of RE‐activated materials. All the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
(89 reference statements)
0
3
0
Order By: Relevance
“…Most of the phosphors were realized by introducing the rare-earth ions into the inorganic hosts, with the resulting colorful emissions being attributed to the 4f–5d and 4f–4f transitions. As a member of lanthanide ions, Eu 3+ ion, which is able to emit an intense narrow red emission at 616 nm triggered by the 5 D 0 → 7 F 2 transition within its intra4f configuration, is thought of a good red-emitting activator. , To date, researchers have demonstrated that the Eu 3+ -ion-based luminescent materials were able to be efficiently pumped by NUV chip and exhibited potential feasibility in white LED applications. From previous literature, it is obvious that the luminescent performance of the rare-earth ions is greatly affected by the host’s phonon energy. , Specially, when the phonon energy is low, the rate of nonradiative transition can be hindered and the possibility of the radiative transition would be promoted, resulting in high luminous efficiency. Consequently, selecting a suitable host is a feasible technique to modify the luminescent behaviors of the rare-earth ions.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the phosphors were realized by introducing the rare-earth ions into the inorganic hosts, with the resulting colorful emissions being attributed to the 4f–5d and 4f–4f transitions. As a member of lanthanide ions, Eu 3+ ion, which is able to emit an intense narrow red emission at 616 nm triggered by the 5 D 0 → 7 F 2 transition within its intra4f configuration, is thought of a good red-emitting activator. , To date, researchers have demonstrated that the Eu 3+ -ion-based luminescent materials were able to be efficiently pumped by NUV chip and exhibited potential feasibility in white LED applications. From previous literature, it is obvious that the luminescent performance of the rare-earth ions is greatly affected by the host’s phonon energy. , Specially, when the phonon energy is low, the rate of nonradiative transition can be hindered and the possibility of the radiative transition would be promoted, resulting in high luminous efficiency. Consequently, selecting a suitable host is a feasible technique to modify the luminescent behaviors of the rare-earth ions.…”
Section: Introductionmentioning
confidence: 99%
“…This effect may result in different changes in crystal symmetry, electric structures, and crystal field strength, which can have great influences on the energy splitting and electronic transition in RE‐activator‐containing perovskites. There have been considerable efforts on investigations of luminescence in RE‐(eg, Eu 3+ , Er 3+ , Pr 3+ , Ce 3+ , and Yb 3+ ) activated perovskite oxides …”
Section: Introductionmentioning
confidence: 99%
“…Eu 3+ is an activator based on its specialties, ie, its emission lines are very simple compared with the other RE ions. Eu 3+ ions substituted for host cations in a host usually exhibit a bright red emission and it can be easily excited by UV‐ and near UV‐radiation which is strongly absorbed by the charge‐transfer (CT) transition of Eu 3+ …”
Section: Introductionmentioning
confidence: 99%